Taqyīm Ta’allum al-Lugah al-Arabiyyah abr al-Intirnit bi Namūżaj Countenence Stake fi Aṡnāi Jāiḥah Kūfīd 19 - Ulin Nuha (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study aims to evaluate about online Arabic language learning at MAN 1 Gunungkidul based on the Decree of the Directorate General of Islamic Education by No. 2791 of 2020 on Emergency Curriculum Guidance at School with the Countenance Stake model. The Data collection techniques are carried out by observation, interview, and documentation. The results of this study are: 1) the learning plan is in the form of RPP content with an online model on Arabic language learning during the Covid-19 Pandemic at MAN 1 Gunung kidul falls into the very good category (84%), 2) the implementation of Arabic learning with online models on Arabic language learning during the Covid-19 Pandemic at MAN 1 Gunungkidul is in very good category (82%), 3) Assessment of Arabic learning with online model on Arabic learning during the Covid-19 Pandemic at MAN 1 Gunungkidul is in the good category (75.26%).